Pengaruh Kompetensi dan Lingkungan Kerja terhadap Kinerja Karyawan di KSU - Hidayah, Nuril; Jatmiko, Udik; Fuad, A. Zaky; Salim, Helmi Agus (Commodities, Journal of Economic and Business, 2025)
This study examines the sustainable economic transformation in rural Indonesia, focusing on Warujayeng Village, East Java, during the post-pandemic era. The research addresses how rural communities integrate traditional practices with modern innovations to achieve economic resilience, challenging conventional modernization paradigms. Employing a qualitative approach with participatory observation, in-depth interviews, and document analysis, the study identifies three adaptation phases: selective resistance, limited experimentation, and hybrid practice institutionalization. Key findings reveal that 72% of traditional traders adopted digital platforms while maintaining interpersonal transactions, and polyculture farming systems showed 23% greater resilience than monocultures during crises. The study introduces the concepts of "culturalized innovation" and "digital embeddedness," emphasizing informal institutions as mediators of innovation. These findings contribute to development theory and suggest culturally sensitive policy frameworks for rural development.